Work Content of General Practitioners in Beijing, China: A Multi-method Study - Yun Wei; Feiyue Wang; Zhaolu Pan; Guanghui Jin; Dawei Wang; Xiaoqin Lu; Qiumei Cao (Frontiers Media S.A., 2022)
BackgroundDespite the dramatic growth of primary care in China, little evidence showed what general practitioner (GP) do and how GP provided medical service in Beijing.ObjectiveThis study aimed to explore the work content of GPs in primary care in Beijing.MethodsA multi-method study was conducted in five community health service institutions using non-participant observation and critical incident technique interview. Eleven GPs was recruited by purpose sampling, with each GP recording details of 100 patient encounters. Health problems of patients and activities of GPs were observed in consultations. Then, critical incident technique interviews were conducted focusing on GPs' works out of clinics and challenge.ResultsA total of 1, 100 patients encounters and 1,897 reasons for encounter (RFEs) were recorded from 11 GPs. There were 1897 RFEs (1.72 per encounter) and 2,762 health problems (2.51 per encounter) from 1,100 encounters during our observation. GPs' work related to consultation was focus on disease diagnoses and treatment. Physical examination and investigations were performed in only 15.5 and 17.1% consultations, respectively. Procedures for chronic disease management were infrequently provided to patients (0.4-26.6%). Time spent in each work process in consultations ranged from 0.68 ± 0.27 min for reservation to 4.00 ± 2.45 min for surgical treatment. In addition to clinical work, there were tasks about health files, contracted family doctor services, health education, teaching students, and scientific research.ConclusionThis study illustrated the complexity of GPs' work and heavy workload in Beijing, China. More attention and effort are needed to develop GPs performance and release GPs' work workload in primary care.